Modulation of VR-HMD-induced cybersickness using cathodal transcranial direct current stimulation: a functional near-infrared spectroscopy study - Yun, Seong Ho; Yeo, Sang Seok; Park, Seo Yoon (Frontiers in Virtual Reality, 2025)
Virtual reality head-mounted displays (VR-HMDs) can induce cybersickness symptoms, including nausea, dizziness, and disorientation, due to sensory conflicts between visual and vestibular inputs. This study investigated the effects of cathodal transcranial direct current stimulation (tDCS) on cybersickness symptoms and cortical activity during VR experiences. Twenty healthy adults were randomly assigned to either the cathodal tDCS group (n = 10) or the sham stimulation group (n = 10). Participants underwent VR rollercoaster exposure while cortical activity was measured using functional near-infrared spectroscopy (fNIRS) before and after 20 min of 2 mA cathodal tDCS applied over the right temporoparietal junction (TPJ). Cybersickness symptoms were assessed using the Simulator Sickness Questionnaire (SSQ). Results showed that cathodal tDCS significantly reduced nausea-related cybersickness symptoms compared to sham stimulation (p < 0.05). fNIRS analysis revealed decreased oxyhemoglobin concentrations in the bilateral superior parietal lobule and angular gyrus following cathodal tDCS, indicating reduced cortical activity in these regions. Between-group comparisons confirmed greater reductions in cortical activity in the right TPJ regions for the cathodal group than for the sham group. These findings suggest that cathodal tDCS over the right TPJ can effectively mitigate cybersickness by modulating cortical activity in brain regions associated with multisensory integration and vestibular processing.